2018
DOI: 10.1186/s12931-018-0769-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations between comorbidities, their treatment and survival in patients with interstitial lung diseases – a claims data analysis

Abstract: BackgroundInterstitial lung diseases (ILDs) are associated with a high burden of disease. However, data on the prognostic impact of comorbidities and comorbidity-related pharmaceutical treatments in patients with various ILDs remain sparse.MethodsUsing longitudinal claims data from a German Statutory Health Insurance Fund, we assessed comorbidity in ILD subtypes and associated drug treatments. Baseline comorbidity was assessed via the Elixhauser Comorbidity Index that was amended by ILD-relevant conditions. Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 49 publications
4
36
1
2
Order By: Relevance
“…One study found that up to 30% of patients with ILD are on BBs for the treatment of co-existing cardiovascular disease and 88.6% of ILD patients with cardiac arrhythmias were on BBs. 46 No study has reported on their efficacy. BBs have occasionally been associated with ILD development 53 but this is an extremely rare complication and should not impact acute AAs management.…”
Section: Beta Blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that up to 30% of patients with ILD are on BBs for the treatment of co-existing cardiovascular disease and 88.6% of ILD patients with cardiac arrhythmias were on BBs. 46 No study has reported on their efficacy. BBs have occasionally been associated with ILD development 53 but this is an extremely rare complication and should not impact acute AAs management.…”
Section: Beta Blockersmentioning
confidence: 99%
“…This can worsen right ventricular systolic function through cardiac myofibril overdistention. As the right Olsson et al 14 Mercurio et al 44 Malacznska-Rajpold et al 36 Durheim et al 45 Schwarzkopf et al 46…”
Section: Beta Blockersmentioning
confidence: 99%
“…For patients with HP, a thorough investigation for the inciting antigen should be performed and, if the antigen can be identified, the patient advised of the importance of antigen avoidance [86]. Management of extra-pulmonary manifestations of disease and identification and treatment of comorbidities can improve patient outcomes [8789].…”
Section: Overall Care Of Patients With Fibrosing Ildsmentioning
confidence: 99%
“…Usually, in many fibrotic ILDs, disease progresses over time and is thus associated with worsened symptoms. ILD patients frequently suffer from comorbid conditions and consequences of the disease, such as pulmonary hypertension, arrhythmias, exercise-induced hypoxemia, and skeletal muscle weakness [4]. Historically, physical activity in patients with ILDs with breathlessness at resting conditions was not recommended.…”
Section: Introductionmentioning
confidence: 99%